Iron-depletion promotes mitophagy to maintain mitochondrial integrity in pathogenic yeast Candida glabrata. Issue 8 (2nd August 2016) - Nagi, Minoru; Tanabe, Koichi; Nakayama, Hironobu; Ueno, Keigo; Yamagoe, Satoshi; Umeyama, Takashi; Ohno, Hideaki; Miyazaki, Yoshitsugu
ABSTRACT: Candida glabrata, a haploid budding yeast, is the cause of severe systemic infections in immune-compromised hosts. The amount of free iron supplied to C. glabrata cells during systemic infections is severely limited by iron-chelating proteins such as transferrin. Thus, the iron-deficiency response in C. glabrata cells is thought to play important roles in their survival inside the host's body. In this study, we found that mitophagy was induced under iron-depleted conditions, and that the disruption of a gene homologous to ATG32, which is responsible for mitophagy in Saccharomyces cerevisiae, blocked mitophagy in C. glabrata . The mitophagic activity in C. glabrata cells was not detected on short-period exposure to nitrogen-starved conditions, which is a mitophagy-inducing condition used in S. cerevisiae . The mitophagy-deficient atg32 Δ mutant of C. glabrata also exhibited decreased longevity under iron-deficient conditions. The mitochondrial membrane potential in Cgatg32 Δ cells was significantly lower than that in wild-type cells under iron-depleted conditions. In a mouse model of disseminated infection, the Cgatg32 Δ strain resulted in significantly decreased kidney and spleen fungal burdens compared with the wild-type strain. These results indicate that mitophagy in C. glabrata occurs in an iron-poor host tissue environment, and it may contribute to the longevity of cells, mitochondrial quality control, and pathogenesis.